Central muscarinic and LPBN mechanisms on sodium intake - Anesio, Augusto [UNESP]; Barbosa, Silas Pereira [UNESP]; De Luca, Laurival A. [UNESP]; de Paula, Patrícia Maria [UNESP]; Colombari, Débora S.A. [UNESP]; Colombari, Eduardo [UNESP]; Andrade, Carina A.F. [UNESP]; Menani, José V. [UNESP] (Elsevier, 2019)
Central cholinergic activation stimulates water intake, but also NaCl intake when the inhibitory mechanisms are blocked with injections of moxonidine (α2 adrenergic/imidazoline agonist) into the lateral parabrachial nucleus (LPBN). In the present study, we investigated the involvement of central M1 and M2 muscarinic receptors on NaCl intake induced by pilocarpine (non-selective muscarinic agonist) intraperitoneally combined with moxonidine into the LPBN or by muscimol (GABAA agonist) into the LPBN. Male Holtzman rats with stainless steel cannulas implanted bilaterally in the LPBN and in the lateral ventricle were used. Pirenzepine (M1 muscarinic antagonist, 1 nmol/1 μl) or methoctramine (M2 muscarinic antagonist, 50 nmol/1 μL) injected intracerebroventricularly (i.c.v.) reduced 0.3 M NaCl and water intake in rats treated with pilocarpine (0.1 mg/100 g of body weight) injected intraperitoneally combined with moxonidine (0.5 nmol/0.2 μL) into the LPBN. In rats treated with muscimol (0.5 nmol/0.2 μL) into the LPBN, methoctramine i.c.v. also reduced 0.3 M NaCl and water intake, however, pirenzepine produced no effect. The results suggest that M1 and M2 muscarinic receptors activate central pathways involved in the control of water and sodium intake that are under the influence of the LPBN inhibitory mechanisms.
Keywords: Cholinergic; Methoctramine; NaCl intake; Parabrachial; Pirenzepine; Sodium appetite